Identification of mRNAs and lncRNAs Involved in the Regulation of Follicle Development in Goat - Zhao, Zhifeng; Zou, Xian; Lu, Tingting; Deng, Ming; Li, Yaokun; Guo, Yongqing; Sun, Baoli; Liu, Guangbin; Liu, Dewu (Frontiers in Genetics, 2020)
Follicular development and maturation has a significant impact on goat reproductive performance, and it is therefore important to understand the molecular basis of this process. The importance of long non-coding RNAs (lncRNAs) in mammalian reproduction has been established, but little is known about the roles of lncRNAs in different follicular stages, especially in goats. In this study, RNA sequencing (RNA-seq) of large follicles (> 10 mm) and small follicles (< 3 mm) of Chuanzhong black goats was performed to investigate the regulatory mechanisms of lncRNAs and mRNAs in follicular development and maturation. A total of 8 differentially expressed lncRNAs (DElncRNAs) and 1,799 DEmRNAs were identified, and the majority of these were upregulated in small follicles. MRO, TC2N, CDO1, and NTRK1 were potentially associated with follicular maturation. KEGG pathway analysis showed that the DEmRNAs involved in ovarian steroidogenesis (BMP6, CYP11A1, CYP19A1, 3BHSD, STAR, LHCGR, and CYP51A1) and cAMP signaling play roles in regulating follicular maturation and developmental inhibition respectively. Five target pairs of DElncRNA-DEmRNA, namely, ENSCHIT00000001255-OTX2, ENSCHIT00000006005-PEG3, ENSCHIT00000009455-PIWIL3, ENSCHIT00000007977-POMP and ENSCHIT00000000834-ACTR3 in co-expression analysis provide a clue in follicular development and maturation of lncRNA-mRNA interaction. Our findings provide a valuable resource for lncRNA studies, and could potentially provide a deeper understanding of the genetic basis and molecular mechanisms of goat follicular development and maturation.